MEMAHAMI MAKNA RELIGIUSITAS/SPIRITUALITAS PADA INDIVIDU DEWASA MUDA MELALUI PHOTOVOICE - Anita Novianty; Evans Garey (Jurnal Psikologi Integratif, 2020)
Early adulthood was indicated by exploring self-identity, including re-questioning the religion belief that was taught by nuclear family since childhood. Most of young adult perceived themselves or by older people as less religious, but spiritual. This study aims to understand the meaning of religiosity/spirituality from a) perspective of their own religion; b) perspective of other religion; and c) their religious experience. Photovoice was applied in this study with various background of participant’s religion including Moslem, Christian, Catholic, Hinduism, Buddhism, and Kong Hu Cu, which selected by snowball sampling. The result showed worship place and activities were mostly chosen as representation of the meaning of religiosity/spirituality from their own religion perspective as well as other religion. Whereas, moment in worship activity and personal experience where they can get through of difficult or unfortunate situation were representation of their religious/spiritual experience. From this study, we can conclude that the institutionalized religion is still play important role in young adult’s spiritual/religious life.